Communication Strategy of Peduly Gotong Royong Foundation in Building Volunteer Re-participation in Surabaya - Ivana Wardana; Jandy Edipson Luik; Daniel Budiana (Petra Christian University, 2024)
Peduly Surabaya is how people called Peduly Gotong Royong Foundation which islocated in Surabaya. Peduly Surabaya started volunteer activities involving external parties inJune 2023. In a month, there are around 3-5 volunteers who return more than twice in thesame month. This statement shows that the level of re-participation in Peduly Surabaya isrelatively high. With a case study method, the case that can be studied from Peduly Surabayais the strategy in attracting volunteers to return to Peduly Surabaya's new volunteer activities.Based on the result, there are six strategies. These six strategies include internal and externalstrategies that are communicated directly or through online media. First, choose amanagement team that is communicative and has high initiative in accordance with Peduly'svalue. Second, consistently communicating various activities online Third, convey the resultsof evaluations and learning from previous activities. Fourth, communication through manymedia. Fifth, familiarize volunteers in creating content about Peduly Surabaya. Sixth,transparency regarding the function of donation contribution